2017
DOI: 10.1038/pr.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of X-linked Toll-like receptor 4 signaling genes in female vs. male neonates

Abstract: Increased expression of IRAK1 could be responsible, in part, for sex-specific responses to infection and subsequent immune advantage in female neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…4D). Female neonates have higher levels of IRAK1 mRNA and protein in cord blood and mononucleated cells compared to males 47 , potentially contributing to reduced infection rates and female-specific immune advantages in infants. However, these scRNAseq analyses are limited by the fact that the sample was taken from one individual and does not contain in vivo stimulated B cells, which may have distinct XCI escape profiles.…”
Section: Discussionmentioning
confidence: 99%
“…4D). Female neonates have higher levels of IRAK1 mRNA and protein in cord blood and mononucleated cells compared to males 47 , potentially contributing to reduced infection rates and female-specific immune advantages in infants. However, these scRNAseq analyses are limited by the fact that the sample was taken from one individual and does not contain in vivo stimulated B cells, which may have distinct XCI escape profiles.…”
Section: Discussionmentioning
confidence: 99%
“…In human, a variant IRAK-1 haplotype with persistent increase of kinase activity was associated with a strong NF-κB activation and a severe inflammation ( 37 39 ). Recently, a study on cord blood cells revealed higher expression of IRAK-1 in female neonates compared to males and this was suggested as an immune advantage for females in infection-induced inflammatory diseases ( 40 ). Whether the overexpression of IRAK-1 is accompanied by an increased kinase activity was not shown in this study.…”
Section: Potential Role Of Toll-like Receptors (Tlrs) and X-linked Inmentioning
confidence: 99%
“…SARS-CoV-2 infection or severity of COVID-19 is yet to be studied and understood. [156][157][158][159]…”
Section: -159mentioning
confidence: 99%